Cervantes and his Don Quixote as an Exemplary Model in Early Modern French Narratives: Sorel, Scarron and Furetière (Rilce. Revista de Filología Hispánica, 2018)
In this paper I shall explore Cervantes’ role as an “exemplary” model for the establishment of the aesthetics of Realism in France, which characterizes the modern novel in the 17th century. Through a comparative analysis, I shall highlight the influence of Don Quixote on the works of Charles Sorel and Paul Scarron (among others). By deploying strategies of parody and satire which are similar to Cervantes’, their novels implied a critical reaction against the heroic and sentimental works by Madeleine de Scudéry and Honoré d’Urfé. At the same time, the authors studied here should be regarded as forerunners to the renewal of the picaresque genre led by Lesage and the moral tales by Marivaux and Diderot.